Shelf-Basin interaction along the East Siberian Sea - Anderson, Leif G.; Björk, Göran; Holby, Ola; Jutterstrom, Sara; Morth, Carl Magnus; O'Regan, Matt; Pearce, Christof; Semiletov, Igor; Stranne, Christian; Stoven, Tim; Tanhua, Toste; Ulfsbo, Adam; et al. (Ocean Science, 2017)
Extensive biogeochemical transformation of organic matter takes place in the shallow continental shelf seas of Siberia. This, in combination with brine production from sea-ice formation, results in cold bottom waters with relatively high salinity and nutrient concentrations, as well as low oxygen and pH levels. Data from the SWERUS-C3 expedition with icebreaker Oden, from July to September 2014, show the distribution of such nutrient-rich, cold bottom waters along the continental margin from about 140 to 180 degrees E. The water with maximum nutrient concentration, classically named the upper halocline, is absent over the Lomonosov Ridge at 140 degrees E, while it appears in the Makarov Basin at 150 degrees E and intensifies further eastwards. At the intercept between the Mendeleev Ridge and the East Siberian continental shelf slope, the nutrient maximum is still intense, but distributed across a larger depth interval. The nutrient-rich water is found here at salinities of up to similar to 34.5, i.e. in the water classically named lower halocline. East of 170 degrees E transient tracers show significantly less ventilated waters below about 150 m water depth. This likely results from a local isolation of waters over the Chukchi Abyssal Plain as the boundary current from the west is steered away from this area by the bathymetry of the Mendeleev Ridge. The water with salinities of similar to 34.5 has high nutrients and low oxygen concentrations as well as low pH, typically indicating decay of organic matter. A deficit in nitrate relative to phosphate suggests that this process partly occurs under hypoxia. We conclude that the high nutrient water with salinity similar to 34.5 are formed on the shelf slope in the Mendeleev Ridge region from interior basin water that is trapped for enough time to attain its signature through interaction with the sediment.